16th International Salon of Invention and Innovation Technologies (ARCHIMEDES) - Noor Syahidah, Sabran (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) once again triumphed at the international level when two of its research projects won gold medals at the 16th International Salon of Invention and Innovation Technologies (ARCHIMEDES) held at Sokolniki Exhibition Center, Moscow, Russia on April 2-5, 2013.